Childhood cancer and parental occupation in Finland. Issue 1 (March 1981) - Hemminki, K; Saloniemi, I; Salonen, T; Partanen, T; Vainio, H
Abstract : A case-control study was conducted of the occupations of parents of children under 15 with diagnosed malignancies. The total series contained all childhood cancers cases reported to the Finnish Cancer Registry during the period 1959-75. The parental occupations, recorded at the time of pregnancy, were collected from maternity welfare centres. The cases were analysed as a singly group or as subgroups according to the diagnoses-brain tumours, leukaemia, and all other malignancies. The maternal occupations found more frequently among cases than controls included farmers' wives (1959-68 only), pharmacists, saleswomen, bakers, and factory work of an vehicle driving, machine repair, painting, and the work of men who gave an academic degree as their occupation. Some of these occupations involve possible exposure to harmful chemicals, although chance correlations cannot be excluded.